Pendampingan Produksi Konten Kreatif dalam Penguatan Branding Digital pada PT Mellcoir Sport Indonesia - Selly Agustin; Faizal Bakhron A.; Bintang Satria P.; Moch. Satrio Dewa N.; Kukuh Sinduwiatmo (Yayasan Literasi Sains Indonesia, 2025)
This community service activity focuses on mentoring creative content production as an effort to strengthen the digital branding of PT Mellcoir Sport Indonesia thru collaboration between students, supervising lecturers, and partner industry representatives. The method used is descriptive qualitative with a participatory and collaborative approach to improve students' practical competencies while also refining the company's visual communication strategies and social media management. This activity includes needs analysis, material design, and content production that aligns with brand character and digital market trends, encompassing photo shoots and promotional video creation. The findings from this activity indicate that direct collaboration based on real-world practices has a significant impact on improving content management, increasing visual consistency, and strengthening audience interaction on social media. Furthermore, this activity is also beneficial in building sustainable synergy between the campus environment and industry, while simultaneously enhancing students' ability to apply visual communication theory directly. The contribution of this activity is expected to serve as an example of best practices for digital-based branding development and effectively support local product empowerment programs. Thus, this collaboration is important to ensure the sustainability of local industry branding strategies in the digital age.